2021
DOI: 10.3390/nu13051708
|View full text |Cite
|
Sign up to set email alerts
|

Considerations for Maximizing the Exercise “Drug” to Combat Insulin Resistance: Role of Nutrition, Sleep, and Alcohol

Abstract: Insulin resistance is a key etiological factor in promoting not only type 2 diabetes mellitus but also cardiovascular disease (CVD). Exercise is a first-line therapy for combating chronic disease by improving insulin action through, in part, reducing hepatic glucose production and lipolysis as well as increasing skeletal muscle glucose uptake and vasodilation. Just like a pharmaceutical agent, exercise can be viewed as a “drug” such that identifying an optimal prescription requires a determination of mode, int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 168 publications
(209 reference statements)
0
5
0
Order By: Relevance
“…However, all people exercised at the same time of day. This is worth considering as a strength since recent work highlights the time of day as an important consideration for molecular adaptations (Sato et al., 2022 ) as well as having potential implications for health (Remchak et al., 2021 ). Given our EC participants engaged in PA earlier in the day, future work ought to consider how exercise time of day aligns with chronotype for health benefit.…”
Section: Discussionmentioning
confidence: 99%
“…However, all people exercised at the same time of day. This is worth considering as a strength since recent work highlights the time of day as an important consideration for molecular adaptations (Sato et al., 2022 ) as well as having potential implications for health (Remchak et al., 2021 ). Given our EC participants engaged in PA earlier in the day, future work ought to consider how exercise time of day aligns with chronotype for health benefit.…”
Section: Discussionmentioning
confidence: 99%
“…51 Alternatively, research indicated that a sedentary lifestyle increased the risk of IR. 52,53 People enjoy recreational PA and therefore are more likely to engage more often or for longer periods of time, leading to less time in sedentary activities. On the other hand, individuals with more work-related PA may need rest after work; therefore, they have more sedentary activities.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, research indicated that a sedentary lifestyle increased the risk of IR 52,53. People enjoy recreational PA and therefore are more likely to engage more often or for longer periods of time, leading to less time in sedentary activities.…”
Section: Discussionmentioning
confidence: 99%
“…The output of Insulin is about 0.5-1.0 U/h beneath the basal situation and will increase about 5 instances after ingestion of meals [16]. A basic advance in keeping up glucose homeostasis and clearing the postprandial glucose load is the capacity of insulin to encourage tissue glucose take-up [17]. The cre-ation of insulin is straightforwardly corresponding to the amount of sugar (starches) burned through.…”
Section: Overview Of Pancreasmentioning
confidence: 99%